Documenting violence and literatures of Latin America. Narrating, distancing and theorizing ourselves - Gasel, Alejandro (Universidad Nacional del Litoral, 2022)
This introduction explains the intentions that guided the construction of this special issue, a study of the relationship between literature and violence in Latin America. Starting from a matrix of research that usually discusses three sets of knowledge produced in the global South on post-dictatorship memories, feminisms and gender, and epistemologies of native communities, a possible axis of research on violence and culture in Latin America is traced through the works of some authors from Brazil, Argentina, Chile and Colombia. This introduction also contains a presentation of the articles of this special issue.